ANALISIS PENGARUH ATRIBUT-ATRIBUT KUALITAS AUDIT TERHADAP KEPUASAN KLIEN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2014)
The study about audit quality has been done. But study that purposed to examine the audit quality have influence to satisfaction is rare done. This research empirically re-examine the effect of audit quality to client satisfaction as Bhen et al. (1997) studies. The primary data of this study received from perception of financial managers or controller, that distributed by mail survey. A 137 manager/controller that registered in BEI Directory sent specially manufacture companyt. The quistionary 45 (32.9 %) gave their respons. The results showed that the were a different result between this study and Bhen et al. (1997).studys attribute that effected client satisfaction, the atribute is strong commitment on audit quality